Economic geography - Dimou, Michel; Schaffar, Alexandra (Magnum Publishing, 2016)
"Economic geography is the study of the location, distribution and spatial organization of economic activities across the world. It represents a traditional subfield of the discipline of geography. However, in recent decades, many economists have also approached the field in ways more typical of the discipline of economics. Economic geography has taken numerous approaches to various dissimilar subject matters, as well as economies of agglomeration, transportation, international trade, development, real estate, gentrification, and globalization. This book gives an understanding of the geographic nature of economic systems and global economic change."--Amazon.